A silicon nitride-based ceramic sheet with dense surface and preparation method thereof

By applying a coating that suppresses the powder mixing on the surface of the silicon nitride ceramic sheet, the hole problem caused by the volatility of the glass phase during the silicon nitride sintering is solved, the density and pressure resistance of the ceramic sheet are improved, and the performance and life of the product are significantly improved.

CN119039010BActive Publication Date: 2025-04-15JIANGSU FERROTEC SEMICON TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411264613.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-04-15
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

During the existing silicon nitride sintering process, the glass phase is prone to volatilization, causing holes to form on the surface of the ceramic sheet, affecting the density and pressure resistance of the ceramic sheet.

Method used

A coating with inhibitory effect is adopted to uniformly control the volatility of the glass phase on the surface of the ceramic sheet by calcining the powder mixing and suppressing the mixing of the powder mixing, thereby increasing the density and pressure resistance of the ceramic sheet.

Benefits of technology

It effectively suppresses the volatility of the glass phase on the surface of the ceramic sheet, increases the density and pressure resistance of the ceramic sheet, and the pressure resistance value can reach 25kv, significantly improving the performance and life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039010B_ABST
    Figure CN119039010B_ABST
Patent Text Reader

Abstract

The invention discloses a silicon nitride-based ceramic sheet with a dense surface and a preparation method thereof, and relates to the technical field of ceramic preparation; the ceramic sheet prepared by the invention is coated with an inhibitory coating, thereby uniformly controlling the volatilization of the glass phase on the surface of the ceramic sheet, avoiding the formation of holes, and improving the density and withstand voltage value of the ceramic sheet. The coating slurry is obtained by mixing and grinding intercalated mixed powder, inhibitory mixed powder, solvent and organic carrier, wherein the inhibitory mixed powder is at least one of magnesium fluoride, magnesium nitride, yttrium fluoride, yttrium nitride and silicon dioxide, adding anhydrous ethanol and Span 85, mixing, calcining and grinding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic preparation, in particular to a silicon nitride-based ceramic piece with a dense surface and a preparation method thereof. Background Art

[0002] Silicon nitride, a compound composed of silicon and nitrogen, boasts high strength, high thermal conductivity, low density, and wear resistance, making it widely used in the new energy sector. With the continuous development of new materials technologies, the application prospects of silicon nitride are becoming increasingly broad. In the electronics field, silicon nitride is used as a ceramic substrate material and packaging material to improve the reliability and performance of electronic devices. Furthermore, silicon nitride can be used in the manufacture of high-temperature semiconductor devices and optoelectronic devices.

[0003] As a strong covalently bonded compound, silicon nitride has a very low diffusion coefficient. Therefore, pure silicon nitride cannot be sintered to a dense consistency. Sintering aids must be added to form a liquid phase during sintering to aid densification. During the sintering process, the sintering aids evaporate easily, causing a large number of pores to form on the surface of the ceramic tile, thereby affecting the ceramic tile's withstand voltage and reducing both the ceramic tile lifespan and yield.

[0004] Therefore, it is urgent to find a silicon nitride-based ceramic sheet with a dense surface and a preparation method thereof. Summary of the Invention

[0005] The purpose of the present invention is to provide a silicon nitride-based ceramic tile with a dense surface and a preparation method thereof, and to provide a coating with an inhibitory effect, so as to uniformly control the volatilization of the glass phase on the surface of the ceramic tile, avoid the formation of holes, thereby improving the density and pressure resistance of the ceramic tile, and solve the problem that the glass phase of the ceramic tile is easily volatilized during the existing conventional silicon nitride sintering process, resulting in the formation of holes on the ceramic tile surface.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a silicon nitride-based ceramic tile with a dense surface comprises the following steps:

[0008] Step S1, preparation of a fired mixed powder: mixing boron nitride and α-phase silicon nitride powders, adding anhydrous ethanol and Span 85 for emulsification and dispersion, and then drying at 80-100° C. to obtain a fired mixed powder;

[0009] Step S2, preparing the mixed powder: adding the mixed powder to a ball mill, then adding anhydrous ethanol and Span 85, ball milling and dispersing, then filter pressing and drying, placing in a muffle furnace, heating to 800-850° C. and calcining for 2-8 hours, grinding after calcination to obtain the mixed powder;

[0010] Step S3, slurry preparation: weighing the intercalated mixed powder, the inhibited mixed powder, the solvent and the organic carrier, mixing, stirring and uniformly grinding to obtain a slurry;

[0011] Step S4, powder coating and sintering: coating the prepared slurry on the surface of the silicon nitride green body, debinding, and sintering in a nitrogen atmosphere for 2-8 hours to obtain a ceramic tile.

[0012] The mass ratio of boron nitride to α-phase silicon nitride is (80-100): (1-20), the particle size D50 of the boron nitride powder is 2-10 μm, and the particle size D50 of the α-phase silicon nitride powder is 0.2-2 μm.

[0013] The mixed powder is at least one of magnesium fluoride, magnesium nitride, yttrium fluoride, yttrium nitride, and silicon oxide;

[0014] The mixed powder particle size D50 is suppressed to 0.2-2μm.

[0015] In step S3, the mass ratio of the intercalated mixed powder to the suppressed mixed powder is (85-100): (2-16). The solvent is at least one of methyl isobutyl ether, diethylene glycol monobutyl ether, terpineol, and N-methylpyrrole.

[0016] In step S3, the organic carrier includes methyl isobutyl ether, ethyl cellulose, butyl benzyl phthalate and Span 85; the mass ratio of methyl isobutyl ether, ethyl cellulose, butyl benzyl phthalate and Span 85 is 9:0.75:0.15:0.1.

[0017] In step S3, the total amount of the sintered mixed powder and the suppressed mixed powder accounts for (30-50) wt% of the slurry, the solvent accounts for (25-35) wt% of the slurry, and the organic vehicle accounts for (25-35) wt% of the slurry.

[0018] In step S3, grinding is performed using a three-roller grinder, with the roller spacing set to 80 μm and then adjusted to 5 μm, the roller speed being 100-300 r / min, and grinding being performed 3-6 times.

[0019] The slurry is coated on the surface of the silicon nitride green body by using one of the processes of spraying, coating, printing and casting, with a coating thickness of 5-35 μm.

[0020] In step S4, the debinding temperature is set to 500-700° C. and kept warm for 2-8 hours; the sintering temperature is set to 1750-1900° C. and the nitrogen pressure is 0.5 MPa-2 MPa.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention discloses a silicon nitride-based ceramic tile with a dense surface and a preparation method thereof. The added mixing-inhibiting powder can form a uniform glass phase vapor pressure on the ceramic tile surface, effectively inhibiting the volatilization of the glass phase during sintering of the ceramic tile, thereby preventing the formation of pores on the ceramic tile surface due to the volatilization of the glass phase, thereby increasing the density and withstand voltage value of the ceramic tile, which can reach 25kV, thereby improving product performance and life.

[0023] The present invention discloses a silicon nitride-based ceramic tile with a dense surface and a preparation method thereof. The added mixing inhibitor powder can inhibit the volatilization of silicon nitride at high sintering temperatures and effectively inhibit the growth of grains on the surface of silicon nitride, thereby reducing the surface roughness of the ceramic tile and improving the peeling force after copper plating, so that the peeling force of 0.4mm copper plating reaches 13.5N / mm. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a microscope photograph of the silicon nitride ink imprint of Example 1;

[0025] Figure 2 This is a microscope photograph of the silicon nitride ink imprint of Example 2;

[0026] Figure 3 This is a microscope photograph of the silicon nitride ink imprint of Example 3;

[0027] Figure 4 This is a microscope photograph of the silicon nitride ink imprint of Example 4;

[0028] Figure 5 A microscopic photograph of a silicon nitride ink imprint of a comparative example;

[0029] Figure 6 This is a metallographic microscope photo of silicon nitride of the comparative example (magnified 500 times);

[0030] Figure 7 This is a metallographic microscope photograph of silicon nitride of Example 3 (magnified 500 times);

[0031] Figure 8 This is an electron microscope photograph of silicon nitride of a comparative example (magnified 2000 times);

[0032] Figure 9 This is an electron microscope photograph of silicon nitride in Example 3 (magnification 2000 times). DETAILED DESCRIPTION

[0033] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0034] Reference Figure 1-9 , the present invention provides the following technical solutions:

[0035] In the experiment, the particle size D50 of boron nitride powder is 2-10 μm, and the morphology is a flake structure, and the particle size D50 of α-phase silicon nitride powder is 0.2-2 μm.

[0036] The steps for preparing silicon nitride green body are as follows:

[0037] 1. Powder ratio: Silicon nitride powder with a particle size of D50 = 0.8um, magnesium oxide and yttrium oxide are prepared into a mixed powder in a mass ratio of 92:4:4;

[0038] 2. Slurry preparation: Take 100g of the mixed powder prepared in step 1, 62.5g of anhydrous ethanol, 62.5g of toluene, 15g of polyvinyl butyral, 5g of dibutyl phthalate, and 2.5g of lecithin and add them to a drum ball mill for ball milling at a speed of 35r / min for 18h, then degas the material;

[0039] 3. Tape casting: After degassing, the slurry is cast using a tape casting machine. The casting temperature range is 30℃, 40℃, 50℃, 60℃, and 50℃. The thickness of the cast green body is 0.45mm.

[0040] 4. Green billet die cutting: Use a die cutting machine to cut the green billet roll into 260×190mm green billets for standby use.

[0041] Among them, the MW of polyvinyl butyral is 120,000-150,000.

[0042] Example 1: This example provides a method for preparing a silicon nitride-based ceramic tile with a dense surface. The specific steps are as follows:

[0043] A method for preparing a silicon nitride-based ceramic tile with a dense surface comprises the following steps:

[0044] Step S1, preparation of a fired mixed powder: 90 g of boron nitride and 10 g of α-phase silicon nitride powder were mixed and placed in an emulsifier, 300 g of anhydrous ethanol and 0.5 g of Span 85 were added for emulsification and dispersion, and then dried at 80° C. to obtain a fired mixed powder;

[0045] Step S2, preparing an inhibitory mixing powder: 1 g of magnesium nitride, 0.5 g of yttrium fluoride, and 0.5 g of silicon oxide were placed in a ball mill, and then 6 g of anhydrous ethanol and 0.05 g of Span 85 were added, and the mixture was dispersed by ball milling. The mixture was then filter-pressed and dried, and placed in a muffle furnace, heated to 850° C. and calcined for 4 h. After calcination, the mixture was finely ground using a jet mill to obtain an inhibitory mixing powder with a particle size D50 = 500 nm;

[0046] Step S3, slurry preparation: weighing raw materials according to 100 g of intercalated mixed powder, 2 g of inhibited mixed powder, 80.5 g of solvent and 86 g of organic carrier, mixing and stirring uniformly, grinding on a three-roll mill, setting the roller pitches to 80 μm, 40 μm, 20 μm, 10 μm, and 5 μm, rolling in this order of roller pitches at a roller speed of 200 r / min to prepare a slurry;

[0047] Step S4, powder coating and sintering: The slurry prepared in step S3 is coated on the surface of the silicon nitride green body using a printing machine, with a wet film thickness of 10 μm. The binder is removed at 550°C, kept warm for 2 hours, and then sintered under a nitrogen pressure of 1.2 MPa at a sintering temperature of 1860°C. The ceramic piece is obtained by keeping warm for 2 hours.

[0048] The solvent is methyl isobutyl ether; the ratio of the organic carrier is: methyl isobutyl ether: ethyl cellulose: butyl benzyl phthalate: Span 85 = 9:0.75:0.15:0.1.

[0049] Example 2: This example provides a method for preparing a silicon nitride-based ceramic tile with a dense surface. The specific steps are as follows:

[0050] A method for preparing a silicon nitride-based ceramic tile with a dense surface comprises the following steps:

[0051] Step S1, preparation of a fired mixed powder: 90 g of boron nitride and 10 g of α-phase silicon nitride powder were mixed and placed in an emulsifier, 300 g of anhydrous ethanol and 0.5 g of Span 85 were added for emulsification and dispersion, and then dried at 80° C. to obtain a fired mixed powder;

[0052] Step S2, preparing an inhibitory mixing powder: 2 g of magnesium nitride, 1 g of yttrium fluoride, and 1 g of silicon oxide were placed in a ball mill, and then 12 g of anhydrous ethanol and 0.05 g of Span 85 were added, and the mixture was dispersed by ball milling. The mixture was then filter-pressed and dried, and then placed in a muffle furnace, heated to 850° C. and calcined for 4 h. After calcination, the mixture was finely ground using a jet mill to obtain an inhibitory mixing powder with a particle size D50 = 500 nm;

[0053] Step S3, slurry preparation: weighing raw materials according to 100 g of intercalated mixed powder, 4 g of inhibited mixed powder, 80.5 g of solvent and 86 g of organic carrier, mixing and stirring uniformly, grinding on a three-roll mill, setting the roller pitches to 80 μm, 40 μm, 20 μm, 10 μm, and 5 μm, rolling in this order of roller pitches at a roller speed of 200 r / min to prepare a slurry;

[0054] Step S4, powder coating and sintering: The slurry prepared in step S3 is coated on the surface of the silicon nitride green body using a printing machine, with a wet film thickness of 10 μm. The binder is removed at 550°C, kept warm for 2 hours, and then sintered under a nitrogen pressure of 1.2 MPa at a sintering temperature of 1860°C. The ceramic piece is obtained by keeping warm for 2 hours.

[0055] The solvent is methyl isobutyl ether; the ratio of the organic carrier is: methyl isobutyl ether: ethyl cellulose: butyl benzyl phthalate: Span 85 = 9:0.75:0.15:0.1.

[0056] Example 3: This example provides a method for preparing a silicon nitride-based ceramic tile with a dense surface. The specific steps are as follows:

[0057] A method for preparing a silicon nitride-based ceramic tile with a dense surface comprises the following steps:

[0058] Step S1, preparation of a fired mixed powder: 95 g of boron nitride and 5 g of α-phase silicon nitride powder were mixed and placed in an emulsifier, 300 g of anhydrous ethanol and 0.5 g of Span 85 were added for emulsification and dispersion, and then dried at 80° C. to obtain a fired mixed powder;

[0059] Step S2, preparing an inhibitory mixing powder: 4 g of magnesium nitride, 2 g of yttrium fluoride, and 2 g of silicon oxide were placed in a ball mill, and then 24 g of anhydrous ethanol and 0.05 g of Span 85 were added, and the mixture was dispersed by ball milling. The mixture was then filter-pressed and dried, and then placed in a muffle furnace, heated to 850° C. and calcined for 4 h. After calcination, the mixture was finely ground using a jet mill to obtain an inhibitory mixing powder with a particle size D50 = 500 nm;

[0060] Step S3, slurry preparation: weighing raw materials according to 100 g of intercalated mixed powder, 8 g of inhibited mixed powder, 80.5 g of solvent and 86 g of organic carrier, mixing and stirring uniformly, grinding using a three-roll mill, setting the roller pitch to 80 μm, 40 μm, 20 μm, 10 μm, and 5 μm, rolling in this roller pitch sequence at a roller speed of 200 r / min to prepare a slurry;

[0061] Step S4, powder coating and sintering: The slurry prepared in step S3 is coated on the surface of the silicon nitride green body using a printing machine, with a wet film thickness of 10 μm. The binder is removed at 550°C, kept warm for 2 hours, and then sintered under a nitrogen pressure of 1.2 MPa at a sintering temperature of 1860°C. The ceramic piece is obtained by keeping warm for 2 hours.

[0062] The solvent is methyl isobutyl ether; the ratio of the organic carrier is: methyl isobutyl ether: ethyl cellulose: butyl benzyl phthalate: Span 85 = 9:0.75:0.15:0.1.

[0063] Example 4: This example provides a method for preparing a silicon nitride-based ceramic tile with a dense surface. The specific steps are as follows:

[0064] A method for preparing a silicon nitride-based ceramic tile with a dense surface comprises the following steps:

[0065] Step S1, preparation of a fired mixed powder: 95 g of boron nitride and 5 g of α-phase silicon nitride powder were mixed and placed in an emulsifier, 300 g of anhydrous ethanol and 0.5 g of Span 85 were added for emulsification and dispersion, and then dried at 80° C. to obtain a fired mixed powder;

[0066] Step S2, preparing an inhibitory mixing powder: 8 g of magnesium nitride, 4 g of yttrium fluoride, and 4 g of silicon oxide were placed in a ball mill, and then 48 g of anhydrous ethanol and 0.05 g of Span 85 were added, and the mixture was dispersed by ball milling. The mixture was then filter-pressed and dried, and then placed in a muffle furnace, heated to 850° C. and calcined for 4 h. After calcination, the mixture was finely ground using a jet mill to obtain an inhibitory mixing powder with a particle size D50 = 500 nm;

[0067] Step S3, slurry preparation: weighing raw materials according to 100 g of intercalated mixed powder, 16 g of inhibited mixed powder, 80.5 g of solvent and 86 g of organic carrier, mixing and stirring uniformly, grinding on a three-roll mill, setting the roller pitches to 80 μm, 40 μm, 20 μm, 10 μm, and 5 μm, rolling in this order of roller pitches at a roller speed of 200 r / min to prepare a slurry;

[0068] Step S4, powder coating and sintering: The slurry prepared in step S3 is coated on the surface of the silicon nitride green body using a printing machine, with a wet film thickness of 10 μm. The binder is removed at 550°C, kept warm for 2 hours, and then sintered under a nitrogen pressure of 1.2 MPa at a sintering temperature of 1860°C. The ceramic piece is obtained by keeping warm for 2 hours.

[0069] The solvent is methyl isobutyl ether; the ratio of the organic carrier is: methyl isobutyl ether: ethyl cellulose: butyl benzyl phthalate: Span 85 = 9:0.75:0.15:0.1.

[0070] Comparative Example: This embodiment provides a method for preparing a silicon nitride-based ceramic tile with a dense surface, and the specific steps are as follows:

[0071] Step S1, preparation of a fired mixed powder: 100 g of boron nitride was placed in an emulsifier, 300 g of anhydrous ethanol and 0.5 g of Span 85 were added for emulsification and dispersion, and then dried at 80° C. to obtain a fired mixed powder;

[0072] Step S2, slurry preparation: weighing raw materials according to 100 g of the intercalated mixed powder, 80.5 g of the solvent and 86 g of the organic carrier, mixing and stirring them uniformly, and grinding them on a three-roll mill with the roller pitches set to 80 μm, 40 μm, 20 μm, 10 μm and 5 μm, rolling them in this order at a roller speed of 200 r / min to prepare a slurry;

[0073] Step S3, powder coating and sintering: The slurry prepared in step S2 is coated on the surface of the silicon nitride green body using a printing machine, with a wet film thickness of 10 μm, and the binder is removed at 550°C. After keeping the temperature for 2 hours, the ceramic tile is sintered under a nitrogen pressure of 1.2 MPa at a sintering temperature of 1860°C and kept warm for 2 hours.

[0074] The solvent is methyl isobutyl ether; the ratio of the organic carrier is: methyl isobutyl ether: ethyl cellulose: butyl benzyl phthalate: Span 85 = 9:0.75:0.15:0.1.

[0075] Table 1 Septum of Examples 1 to 4 and Comparative Examples Burnt mixed powder ,inhibition Mixed powder Ratio of raw materials

[0076]

[0077] Test method:

[0078] 1. Pore characterization

[0079] Take the ceramic pieces prepared in Examples 1-4 and Comparative Example and soak them in black ink for 5 minutes, then use pure water ultrasonic cleaning, anhydrous ethanol ultrasonic cleaning, and after drying, use a microscope to observe the voids on the ceramic surface at a magnification of 60 times. The test results are shown in Figure 1-5 .

[0080] 2. Density test

[0081] The density was tested by the displacement method using an analytical balance.

[0082] 3. Roughness test

[0083] The test was carried out using a roughness tester TR200.

[0084] 4. Voltage test

[0085] Place the tile in a high-voltage test environment, and test the DC voltage from 15KV to 25KV, with an interval of 1kV each time and a test time of 10s. If there is a voltage breakdown, the test is suspended and the value at this time is its withstand voltage value.

[0086] 5. Peel force test

[0087] The ceramic sheets prepared in Examples 1-4 and the comparative example were printed with a 15 μm thick layer of Ag-Cu-Ti active metal slurry on their surfaces, where the mass ratio of Ag, Cu, and Ti in the active metal slurry was 65:30:5. A 0.4 mm copper foil was then laminated on the solder using hot pressing technology. Finally, a test pattern was sintered, photolithographically, and etched, and a peel strength test was performed using a peel strength tester.

[0088] Table 2 Experimental data of comparative test of Examples 1-4

[0089]

[0090] Through the above data and comparison Figure 1-5 The surface of the ceramic tile made in the comparative example has more pores, resulting in a lower density and a withstand voltage value of only 17kv. The surface roughness is large, and the bending strength of the ceramic tile is also low, resulting in a low copper clad peeling force; the ceramic tiles made in Examples 3 and 4 have no pores on the surface, a higher density, and a relatively high withstand voltage value. Inhibiting powder mixing can well inhibit the volatilization of silicon nitride on the surface of the ceramic tile at high temperature, and can effectively inhibit the growth of silicon nitride surface grains, thereby reducing the surface roughness of the ceramic tile and improving the copper clad peeling force, especially the withstand voltage value of Example 3 reaches 25kv, and the peeling force can reach 13.5N / mm; It can be seen that adding inhibitory powder mixing can significantly reduce pores, improve density and withstand voltage value.

[0091] from Figure 6 、 Figure 7 From the metallographic microscope photos magnified 500 times, it can be seen that the glass phase on the surface of the ceramic piece made in the comparative example evaporates unevenly, aggregates, and forms a larger glass state, resulting in part of the surface being filled with no glass phase, such as Figure 6 As shown in the red circled area, pores are formed; no glass phase aggregation occurs on the surface of the ceramic tile prepared in Example 3, and the glass phase is uniformly suppressed inside the ceramic tile.

[0092] from Figure 8 、 Figure 9 From the electron microscope photos magnified 2000 times, it can be seen that the glass phase of the ceramic pieces made in the comparative example is unevenly distributed. The red circled area has more pores due to the volatilization of the glass phase, and the grains grow abnormally, resulting in greater roughness. In Example 3, the volatilization of the glass phase of the ceramic piece is suppressed by suppressing the addition of mixed powder, so that the glass phase is evenly distributed. Due to the glass phase filling, no obvious pores are seen, the grains grow evenly, and no abnormal growth is observed. Therefore, the density of the ceramic piece in Example 3 is greater and the surface roughness is smaller.

[0093] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.

Claims

1. A method for preparing a surface dense silicon nitride-based ceramic sheet, characterized in that: The specific steps are: Step S1, preparation of intercalated mixed powder: mixing boron nitride and α-phase silicon nitride powder, adding anhydrous ethanol and Span 85 for emulsification and dispersion, and then drying at 80-100° C. to obtain intercalated mixed powder; Step S2, preparing mixed powder: adding the mixed powder to a ball mill, adding anhydrous ethanol and Span 85, performing ball milling dispersion, then filtering and drying, placing in a muffle furnace, heating to 800-850° C. and calcining for 2-8 hours, grinding after calcination to obtain mixed powder; the mixed powder is at least one of magnesium fluoride, magnesium nitride, yttrium fluoride, yttrium nitride, and silicon oxide; Step S3, slurry preparation: weigh the intercalated mixed powder, the inhibited mixed powder, the solvent and the organic carrier, stir them evenly, grind them, and obtain slurry; Step S4, powder coating and sintering: coating the prepared slurry on the surface of the silicon nitride green body, debinding and sintering in a nitrogen atmosphere, and keeping the temperature for 2-8 hours to obtain a ceramic sheet; In step S3, the mass ratio of the sintered mixed powder to the suppressed mixed powder is (85-100):(2-16).

2. The method for preparing a surface dense silicon nitride-based ceramic sheet according to claim 1, characterized in that: The mass ratio of the boron nitride to the α-phase silicon nitride is (80-100):(1-20), the particle size D50 of the boron nitride powder is 2-10 μm, and the particle size D50 of the α-phase silicon nitride powder is 0.2-2 μm.

3. The method for preparing a surface dense silicon nitride-based ceramic sheet according to claim 1, characterized in that: The mixed powder particle size D50 is suppressed to 0.2-2μm.

4. The method for preparing a surface dense silicon nitride-based ceramic sheet according to claim 1, characterized in that: In step S3, the solvent is at least one of methyl isobutyl ether, diethylene glycol monobutyl ether, terpineol, and N-methylpyrrole.

5. The method for preparing a surface dense silicon nitride-based ceramic sheet according to claim 1, characterized in that: In step S3, the organic carrier includes methyl isobutyl ether, ethyl cellulose, butyl benzyl phthalate and Span 85; the mass ratio of methyl isobutyl ether, ethyl cellulose, butyl benzyl phthalate and Span 85 is 9:0.75:0.15:0.

1.

6. The method for preparing a silicon nitride-based ceramic sheet with a dense surface according to claim 1, characterized in that: The sum of the intercalated mixed powder and the inhibited mixed powder accounts for (30-50) wt% of the slurry, the solvent accounts for (25-35) wt% of the slurry, and the organic carrier accounts for (25-35) wt% of the slurry.

7. The method for preparing a surface dense silicon nitride-based ceramic sheet according to claim 1, characterized in that: In step S3, grinding is performed using a three-roller grinder, with the roller spacing set to 80 μm and then adjusted to 5 μm, the roller speed being 100-300 r / min, and grinding being performed 3-6 times.

8. The method for preparing a silicon nitride-based ceramic sheet with a dense surface according to claim 1, characterized in that: The slurry is coated on the surface of the silicon nitride green body by using one of the processes of spraying, coating, printing and casting, and the coating thickness is 5-35 μm.

9. The method for preparing a silicon nitride-based ceramic sheet with a dense surface according to claim 1, characterized in that: In step S4, the debinding temperature is set to 500-700°C and kept warm for 2-8h; the sintering temperature is set to 1750-1900°C and the nitrogen pressure is 0.5-2MPa.

Citation Information

Patent Citations

  • Structure and preparation method of porous silicon nitride ceramic surface coating

    CN113816771A